The role of combining the intellectual and emotional culture of the teacher in the learning process using distance technology (Pedagogy of Higher and Secondary Education, 2021)
The article is about the value of a harmonious combination of teacher's intellectual and emotional culture for effective learning with use of distance technologies.
Keywords: interaction; feedback; control of knowledge; learning technologies; distance technologies